Ultrafast excited-state dynamics of rhenium(I) photosensitizers [Re(Cl)(CO)3(N,N)] and [Re(imidazole)(CO)3(N,N)]+: diimine effects - El Nahhas, Amal; Consani, Cristina; Blanco-Rodríguez, Ana María; Lancaster, Kyle M; Braem, Olivier; Cannizzo, Andrea; Towrie, Michael; Clark, Ian P; Zális, Stanislav; Chergui, Majed; Vlcek, Jr, Antonín (Inorganic chemistry, 2011)
Femto- to picosecond excited-state dynamics of the complexes [Re(L)(CO)(3)(N,N)](n) (N,N = bpy, phen, 4,7-dimethyl-phen (dmp); L = Cl, n = 0; L = imidazole, n = 1+) were investigated using fluorescence up-conversion, transient absorption in the 650-285 nm range (using broad-band UV probe pulses around 300 nm) and picosecond time-resolved IR (TRIR) spectroscopy in the region of CO stretching vibrations. Optically populated singlet charge-transfer (CT) state(s) undergo femtosecond intersystem crossing to at least two hot triplet states with a rate that is faster in Cl (∼100 fs)(-1) than in imidazole (∼150 fs)(-1) complexes but essentially independent of the N,N ligand. TRIR spectra indicate the presence of two long-lived triplet states that are populated simultaneously and equilibrate in a few picoseconds. The minor state accounts for less than 20% of the relaxed excited population. UV-vis transient spectra were assigned using open-shell time-dependent density functional theory calculations on the lowest triplet CT state. Visible excited-state absorption originates mostly from mixed L;N,N(•-) → Re(II) ligand-to-metal CT transitions. Excited bpy complexes show the characteristic sharp near-UV band (Cl, 373 nm; imH, 365 nm) due to two predominantly ππ*(bpy(•-)) transitions. For phen and dmp, the UV excited-state absorption occurs at ∼305 nm, originating from a series of mixed ππ* and Re → CO;N,N(•-) MLCT transitions. UV-vis transient absorption features exhibit small intensity- and band-shape changes occurring with several lifetimes in the 1-5 ps range, while TRIR bands show small intensity changes (≤5 ps) and shifts (∼1 and 6-10 ps) to higher wavenumbers. These spectral changes are attributable to convoluted electronic and vibrational relaxation steps and equilibration between the two lowest triplets. Still slower changes (≥15 ps), manifested mostly by the excited-state UV band, probably involve local-solvent restructuring. Implications of the observed excited-state behavior for the development and use of Re-based sensitizers and probes are discussed.